A techno-economic comparison of three process routes for the treatment of Gamsberg zinc ore - Dlamini, Zethu (Centre for Bioprocess Engineering Research, 2015)
There is an abundant availability of zinc sulphide (sphalerite) ore (160 million tons at 7.40 % Zn) at Gamsberg, Northern Cape in South Africa. The ore body is South Africa’s greatest unexploited base metal resource. Regardless of its size, the low zinc and high manganese content of the sphalerite combined with the low zinc price prohibits the development of the deposit. Sphalerite is the most common zinc mineral, hence 95 % of the world’s zinc production is from this mineral. Sphalerite is currently processed by crushing-milling-flotation, followed by the roast-leach-electrowinning (RLE) process. This route has major detrimental impacts on the environment, it produces SO2, and cannot treat ores of low grade or higher complexity. Therefore, alternative processes are being sought in order to circumvent the RLE process. This study compares three different process routes in the context of processing ore from the Gamsberg deposit for refining 3.4 million tpa ore in order to produce special high grade (SHG) zinc (>99.995% Zn). These routes include heap leaching and refining locally (route 1), preparing a flotation concentrate and refining it locally (route 2) and lastly, preparing a flotation concentrate and shipping it for toll refining in Europe (route 3). Zinc heap leaching has not yet been commercialised due to the absence of solvent extraction reagents which can selectively extract zinc from a low tenor acidic pregnant leach solution without incorporating the neutralization stage. Therefore, route 1 has higher risk as compared to the other routes. A desktop model which provides a comparison of capital cost, operating cost, NPV, IRR and PVR has been developed. Parameters such as average zinc grade, process recovery and zinc price are provided as inputs. The effects of fluctuations in important parameters such as working capital, and zinc price on NPV are assessed using Matlab.